Evaluation of Blue Cupressus Arizona Cone in Automotive Brake Pad Biocomposite - Hicri Yavuz (BioResources, 2023)
Recently, new brake pads have been developed using sustainable materials that are not harmful to the environment. In this study, the effect of using blue-colored Cupressus arizonica cones was determined as a friction modifier in brake pad composites. Four different samples were prepared by grinding the cone material. The samples’ physical and chemical properties and performances were compared, and finally, their microscopic analyses were visualized by scanning electron microscopy. Maximum friction coefficient and minimum wear rate are required for brake pads. The maximum friction coefficient of 0.39 and the minimum wear rate of the samples containing Cupressus arizonica were obtained in the 0.124X10-7 cm3/Nm BCA3 sample. When the brake pads developed from lignocellulosic biomass were compared, it was determined that the BCA3 sample met the most reasonable performance values.